1961
DOI: 10.1017/s0022172400038730
|View full text |Cite
|
Sign up to set email alerts
|

An environmental survey of bakehouses and abattoirs for salmonellae

Abstract: 1. Moore's gauze swabs have, in our hands, been shown to be a reliable instrument for the survey of salmonella infection in the environment of two food premises.2. A large bakery was demonstrated to be regularly contaminated with salmonellae. Thirty-one floor gully swabs out of 111 (27·9%) were positive for salmonellae. Little spread of infection to the general public was experienced.3. Staff infection with salmonellae was shown to occur in this bakery. Fifteen positive specimens of staff sewage out of 93 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

1961
1961
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 15 publications
2
18
0
Order By: Relevance
“…The bakery survey led to a similar study of Glamorgan abattoirs in 1957-9. In this investigation, phagetyping of strains of S. typhimurium enabled a detailed comparison to be made between abattoir and human isolations. The timing of recovery of the same phage-types from abattoir and man strongly suggested a causal association (Harvey & Phillips, 1961). Gauze swabs also proved of value in demonstrating the presence of S. typhimurium, type 12, in the environment of 15 out of 54 shops during an outbreak of salmonella food poisoning in Cardiff in 1960.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The bakery survey led to a similar study of Glamorgan abattoirs in 1957-9. In this investigation, phagetyping of strains of S. typhimurium enabled a detailed comparison to be made between abattoir and human isolations. The timing of recovery of the same phage-types from abattoir and man strongly suggested a causal association (Harvey & Phillips, 1961). Gauze swabs also proved of value in demonstrating the presence of S. typhimurium, type 12, in the environment of 15 out of 54 shops during an outbreak of salmonella food poisoning in Cardiff in 1960.…”
Section: Introductionmentioning
confidence: 93%
“…This incident led us to initiate a swab survey of bakehouses in . The investigation demonstrated the entry of salmonellas in raw ingredients of confectionery manufacture and the existence of minor or latent infections in members of bakery staff (Harvey, 1957;Harvey & Phillips, 1961). The bakery survey led to a similar study of Glamorgan abattoirs in 1957-9. In this investigation, phagetyping of strains of S. typhimurium enabled a detailed comparison to be made between abattoir and human isolations.…”
Section: Introductionmentioning
confidence: 99%
“…Some samples of human sewage from Cardiff abattoir were also examined. The results are given in (Harvey & Phillips, 1961). From the records of the Veterinary Investigation Department, Cardiff, it was found that type 12 had been isolated from animals on three farms in SouthWales in 1959-60.…”
Section: Investigation Of the Outbreakmentioning
confidence: 98%
“…In a previous group of related cases due to S. typhi-murium, 1 a var. 3 (Harvey & Phillips, 1961), it had been possible to isolate the organism from farm animals in South Wales, from abattoir samples and from local human infections. In the present outbreak, we wished to follow the path of infection to retail food premises.…”
Section: Investigation Of the Outbreakmentioning
confidence: 99%
See 1 more Smart Citation